Narratives about the communication, limits and hierarchies in children with separated parents - Luz Elena Pinzón Sanabria; Gabriela Vanegas Pérez (Interacciones)
The present research describe the narratives about communication, limits and hierarchies of five children with separated parents, between eight and twelve years old, with the goal of contributing to the understanding of this specific kind of family dynamics, using theoretical elements of the systemic approach and corresponds to a qualitative, descriptive methodology with a narrative design, using the open interviews as technique to collect the information. As a relevant finding, it was found that separation is not a communicative topic in the family, parents rarely talk or interact with each other, they do not reach agreements for raising their children and they do not create any effective parental unity. The mother is in charge for setting limits to the children, and she heads the hierarchy, fully assuming parenting. The separated father does not participate in the pattern of authority, he is not either part of the hierarchical organization, generating that the equal position in the hierarchy is occupied by the mother and the new partner.The members of the family have not elaborated the separation yet, as a consequence, to the difficulties to elaborate the divorce on the part of the children, a relational and emotional tension is added with the new spouses of the parents.